The Stochastic Multiresonance Phenomenon in Excitatory-Inhibitory Neuronal Network - Xie, Changzhi; Li, Huiyan; Sun, Xiaojuan (Journal of Applied Nonlinear Dynamics, 2026)
In biological neuronal systems, information propagation and processing are based on signal detection. Stochastic resonance (SR) is an universal phenonmenon for detecting information in nonlinear dynamic systems. In this paper, we investigate the influence of coupling strength from inhibitory neurons on stochastic resonance (SR) in small-world neuronal networks. Each neuron is described as FitzHugh-Nagumo (FHN) model. The main results report that multiple optimal noise could induce stochastic resonance (SR), which is referred as stochastic multiresonance(SMR), and inhibitory neurons could either destroy stochastic multiresonance(SMR) or turn stochastic multiresonance(SMR) to stochastic resonance(SR) in neuronal network.